Multipodal insulin mimetics built on adamantane or proline scaffolds - Hajduch, Jan; Fabre, Benjamin; Klopp, Benjamin; Pohl, Radek; Buděšínský, Miloš; Šolínová, Veronika; Kašička, Václav; Köprülüoglu, Cemal; Eyrilmez, Saltuk Mustafa; Lepšík, Martin; Hobza, Pavel; Mitrová, Katarína; et al. (Bioorganic chemistry, 2021)
Multi-orthogonal molecular scaffolds can be applied as core structures of bioactive compounds. Here, we prepared four tri-orthogonal scaffolds based on adamantane or proline skeletons. The scaffolds were used for the solid-phase synthesis of model insulin mimetics bearing two different peptides on the scaffolds. We found that adamantane-derived compounds bind to the insulin receptor more effectively (Kd value of 0.5 μM) than proline-derived compounds (Kd values of 15-38 μM) bearing the same peptides. Molecular dynamics simulations suggest that spacers between peptides and central scaffolds can provide greater flexibility that can contribute to increased binding affinity. Molecular modeling showed possible binding modes of mimetics to the insulin receptor. Our data show that the structure of the central scaffold and flexibility of attached peptides in this type of compound are important and that different scaffolds should be considered when designing peptide hormone mimetics.
Keywords: Animals; Molecular Dynamics Simulation; Rats; Kinetics; stabilita proteinů; vazebná místa; Protein Structure, Quaternary; vazba proteinů; Solid-Phase Synthesis Techniques; Protein Stability; lidé; Proline; simulace molekulární dynamiky; prolin; Insulin; stereoizomerie; Stereoisomerism; Receptor, Insulin; Adamantane; techniky syntézy na pevné fázi; krysa rodu Rattus; kvarterní struktura proteinů; adamantan; zvířata; receptor inzulinu; inzulin; Protein Binding; kinetika; Binding Sites; Humans